Damping structural adhesive as well as preparation method and application thereof

By adopting shock absorbing structural glue with specific composition and preparation methods, the problem of poor mechanical strength of existing shock absorbing glue is solved, and the characteristics of high elasticity, high strength and high toughness are achieved, ensuring effective shock absorption and bonding performance in vehicle applications.

CN119709052APending Publication Date: 2025-03-28JINAN HANSIMAN TIMES TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411620280.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing shock absorber for vehicles has poor mechanical strength and cannot have both high elasticity, high strength and high toughness, resulting in the risk of cracking of adhesive components in actual applications.

Method used

The shock-absorbing structural glue consisting of plasticizers, PVC paste resins, nano-calcium, PVC stabilizers, mixed rubbers, epoxy resins, sealed polyamides and carbon black are used to improve the mechanical properties and adhesive properties of the colloid through specific preparation methods and component ratios.

Benefits of technology

The high elasticity, high strength and high toughness of shock-absorbing structural adhesive is achieved, ensuring that vibration energy can be effectively absorbed and dispersed in vehicle applications, providing good shock absorption and sound insulation, and improving the firmness and durability of bonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709052A_ABST
    Figure CN119709052A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of damping materials, and discloses a damping structural adhesive, and a preparation method and application thereof. The damping structural adhesive is composed of a plasticizer, PVC paste resin, nano calcium, a PVC stabilizer, mixed rubber, epoxy resin, closed polyamide and carbon black. The structural damping rubber provided by the invention is black single-component thermocuring type damping rubber. The adhesive does not flow at high temperature, and the cured adhesive layer is tough. The cable is good in oil resistance, water resistance, acid and alkali resistance and heat resistance, low in odor and environment-friendly. The damping structural adhesive is prepared from different adhesive raw materials, so that the technological process is simplified, and the cost of the whole automobile is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of shock-absorbing materials, and in particular relates to a shock-absorbing structural adhesive, a preparation method and an application thereof. Background Art

[0002] Shock-absorbing rubber for vehicles is a rubber product mainly used in automobile suspension systems to reduce vibration and impact during driving and improve ride comfort and safety. Shock-absorbing rubber can reduce the vibration of the vehicle body to a certain extent, reduce the noise generated by the suspension system, and thus improve driving comfort; by buffering the pressure of road bumps on the shock-absorbing system, shock-absorbing rubber helps reduce the wear of the automobile shock-absorbing system and prolong its service life; the use of shock-absorbing rubber can improve the stability of the vehicle, improve handling, and in some cases help shorten the braking distance. The shock-absorbing rubber for vehicles in the prior art is generally used for sealing and shock absorption. However, the technical defect of the shock-absorbing rubber for vehicles in the prior art is poor mechanical strength, which limits the practical application of the shock-absorbing rubber for vehicles in the prior art.

[0003] In order to improve the problem of low bonding strength and poor mechanical strength, the existing invention patent: Composite modified epoxy resin structural adhesive and composite modifier and structural adhesive preparation method (publication number CN108048007A, public (announcement) date: 20180518) discloses that the structural adhesive is composed of components A and B. Among them, component A includes 60-75 parts of bisphenol A epoxy resin, 5-15 parts of polyurethane prepolymer compound, and 8-15 parts of active diluent in parts by weight; component B includes 8-15 parts of curing agent in parts by weight. The preparation method of the polyurethane prepolymer compound is to obtain it by incomplete reaction of polyether polyol and polyphenyl polymethyl polyisocyanate. The preparation method of the structural adhesive is to stir component A and component B evenly. However, the technical defect of the invention is that the structural adhesive has high strength, high brittleness, lacks elasticity, cannot play a role in shock absorption of the vehicle body, and may also cause the risk of cracking of the bonded components due to vibration during the use of the vehicle.

[0004] Therefore, providing a shock-absorbing structural adhesive that has shock absorption, high elasticity, high strength, and high toughness is of practical significance for vehicle engineering. Summary of the invention

[0005] In order to overcome the problems existing in the related art, the disclosed embodiments of the present invention provide a shock-absorbing structural adhesive, a preparation method and an application. The purpose of the present invention is to provide a shock-absorbing structural adhesive product with high elasticity, high strength and high toughness. The technical solution is as follows:

[0006] Shock-absorbing structural adhesive is composed of the following substances:

[0007] Plasticizer: 187.5g-312.5g;

[0008] PVC paste resin: 135g-225g;

[0009] Nano calcium: 187.5g-312.5g;

[0010] PVC stabilizer: 15g-25g;

[0011] Compound rubber: 67.5g-112.5g

[0012] Epoxy resin: 75g-125g;

[0013] Closed polyamide: 37.5g-62.5g;

[0014] Carbon black: 7.5g-12.5g.

[0015] Furthermore, the mixed rubber is nitrile.

[0016] Another object of the present invention is to provide a preparation method for preparing the shock-absorbing structural adhesive, the method comprising:

[0017] S1, adding plasticizer, PVC paste resin, nano calcium, mixed rubber and carbon black into a kneader;

[0018] S2, discharging and grinding, adjusting the feeding speed of the grinder and the discharging auger speed of the kneader, and putting the mixed materials into the stirring kettle;

[0019] S3, adding PVC stabilizer into the stirring kettle and starting the reactor;

[0020] S4, weighing epoxy resin and blocked polyamide, adding all materials and stirring;

[0021] S5, start stirring and start vacuum;

[0022] S6, stop stirring, lift the reactor, scrape off the stirring teeth, and discharge the material into cans.

[0023] In step S1, the kneading machine is adjusted to 35-45 Hz for kneading for 60 minutes.

[0024] In step S2, the grinding machine feed speed is 25-30 Hz.

[0025] In step S3, the temperature in the reactor is lowered to below 40°C, materials are added, the wall is scraped at 15-20Hz, and stirring is performed for 60min.

[0026] In step S4, the scraping speed of the stirring is started to be 15-20 Hz, and the stirring time is 30 minutes.

[0027] In step S5, when stirring is turned on, the rotation speed is adjusted to 10-12 Hz; and vacuuming is turned on for 90 minutes.

[0028] Further, in step S3, the preparation method of the PVC stabilizer includes: using the symbiotic reaction technology to mix the trisalt, the disalt and the metal soap in the PVC paste resin reaction system with the initial crystal size and various lubricants to ensure that the PVC stabilizer is fully dispersed in the PVC paste resin system to obtain a composite lead salt heat stabilizer, i.e., a PVC stabilizer.

[0029] In step S4, the method for preparing blocked polyamide includes:

[0030] Ultrasonic dispersion; stirring dispersion; water bath coating; reflux drying;

[0031] The ultrasonic dispersion comprises: adding the polyamide into a beaker containing anhydrous ethanol, and then ultrasonicating the polyamide for 1 h to 3 h at a power of 1000 W using an ultrasonic instrument;

[0032] The stirring and dispersing comprises: stirring and dispersing the mixed solution with an appropriate amount of organic solvent, the speed of the stirrer is 500r / min-800r / min, the time is 10-15min, and the organic solvent is one of n-hexane, cyclohexane, benzene, toluene, xylene, petroleum ether, and solvent gasoline;

[0033] The water bath coating comprises: adding the solution after stirring and dispersing into a three-necked flask, stirring and heating in a water bath at 55-85° C. at 300-500 r / min for 2-4 hours to complete the sealing process;

[0034] The reflux drying comprises: pouring out the solution after water bath sealing, obtaining the precipitated material by centrifuge, and then drying it in a drying oven at 60-85° C. for 6-10 hours; and refluxing and recovering ethanol and organic solvent according to different boiling points, and storing the sample at room temperature after drying to obtain a closed polyamide.

[0035] Another object of the present invention is to provide an application of a shock-absorbing structural adhesive in the structural bonding of a shock-isolating part of a vehicle body, and the shock-absorbing structural adhesive adopts the shock-absorbing structural adhesive.

[0036] Another object of the present invention is to provide an application of a shock-absorbing structural adhesive in the structural bonding of the seismic isolation part of a workshop component, and the shock-absorbing structural adhesive adopts the shock-absorbing structural adhesive.

[0037] In combination with all the above technical solutions, the beneficial effects of the present invention are as follows: the structural shock-absorbing adhesive provided by the present invention is a black single-component heat-curing shock-absorbing adhesive. The present invention prepares a shock-absorbing structural adhesive from different adhesive raw materials, simplifies the process flow, and saves the cost of the whole vehicle.

[0038] The main function of plasticizers is to improve the processing properties of rubber and the physical properties of the final product, reduce the glass transition temperature of rubber, increase its flexibility and ductility, make rubber more elastic and plastic, and help ensure that rubber can effectively absorb energy and provide cushioning when subjected to impact or vibration. In addition, plasticizers can also adjust the hardness and temperature resistance of shock-absorbing rubber to adapt it to different application environments and working conditions. In the formulation of shock-absorbing rubber, the use of plasticizers can improve the low-temperature performance and fatigue resistance of rubber.

[0039] PVC paste resin can provide elasticity and toughness, which helps the shock-absorbing adhesive absorb energy when it is impacted and reduce the force transmitted to the connected object. In addition, PVC paste resin can also give the shock-absorbing adhesive good processing performance and stability, ensuring that the shock-absorbing adhesive maintains its performance in different environments.

[0040] As a reinforcing filler, nano calcium can significantly improve the mechanical properties of shock-absorbing rubber. It can improve the tensile strength, elongation at break and tensile adhesion of the colloid, while increasing the elastic recovery rate and tensile modulus of the colloid. The introduction of nano calcium can improve the processing performance of shock-absorbing rubber, such as accelerating the cross-linking reaction of the rubber, improving the thixotropy of the system, enhancing dimensional stability, and improving the mechanical properties of the rubber. The high filling amount and good dispersibility of nano calcium help reduce the use of other raw materials, thereby reducing production costs.

[0041] PVC stabilizers are used to increase the stability of polyvinyl chloride (PVC) to prevent it from decomposing and degrading during processing and use, so that PVC will not burn and become mushy under high-temperature baking conditions. Since PVC is prone to thermal degradation at high temperatures, stabilizers can absorb and neutralize free radicals generated by thermal decomposition to prevent further breakage of the molecular chain. The antioxidants in the stabilizer can capture free radicals, while the metal salts in the stabilizer can neutralize the generated acid to avoid further reactions.

[0042] The main function of compound rubber (nitrile) is elasticity, and it is the main component of shock absorption. Compound rubber (nitrile) has good mechanical strength, which helps to improve the overall performance of shock-absorbing rubber, enabling it to more effectively absorb and disperse vibration energy; and the colloid is elastic after curing, which has a good shock-absorbing and sound-insulating effect.

[0043] Epoxy resin E54 is used as a strength component in shock-absorbing adhesives. After the colloid is cured, the bonding performance ensures the firmness of the bonding; this is usually related to its characteristics as a high molecular polymer. Epoxy resin is often used as a matrix material for adhesives and composite materials due to its excellent bonding performance, chemical stability and electrical insulation properties. In shock-absorbing adhesives, epoxy resin E54 can provide the necessary structural strength and elasticity, help absorb and disperse vibration energy, and reduce the impact force transmitted to the structure. In addition, the curing characteristics of epoxy resin enable the shock-absorbing adhesive to form a three-dimensional network structure after curing, improving its overall mechanical properties and durability.

[0044] Blocked polyamide is stable at room temperature and coexists with epoxy resin. After being unblocked at high temperature, it serves as a curing component of epoxy resin and is a tackifying component of PVC. In shock-absorbing adhesives, blocked polyamide usually plays a role in enhancing material performance. Blocked polyamide can provide good mechanical strength, heat resistance and chemical stability. These properties are very important for shock-absorbing adhesives because they can ensure that the adhesive maintains its shape and function when subjected to vibration or impact, while resisting high temperature and chemical corrosion. In addition, blocked polyamide can also improve the bonding properties of shock-absorbing adhesives, allowing the adhesive to adhere more firmly to the bonded surface, thereby providing an effective shock-absorbing effect.

[0045] Carbon black is used to adjust thixotropic color.

[0046] In summary, the structural shock-absorbing adhesive provided by the present invention is a black single-component heat-curing shock-absorbing adhesive. It is thixotropic, does not flow at high temperatures, and has good toughness of the adhesive layer after curing. It is oil-resistant, water-resistant, acid-resistant, alkali-resistant, and heat-resistant, has low odor, is environmentally friendly, and has good mechanical properties. The present invention prepares different adhesive raw materials into a shock-absorbing structural adhesive, simplifies the process flow, and saves the cost of the entire vehicle. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The accompanying drawings herein are incorporated in and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the description, serve to explain the principles of the present disclosure;

[0048] Figure 1 It is a flow chart of a method for preparing a shock-absorbing structural adhesive provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0049] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.

[0050] The innovation of the present invention is that the present invention combines the elasticity and toughness requirements of the shock-absorbing adhesive, takes into account the strength and hardness requirements of the structural bonding, and effectively integrates the advantages of good elasticity and toughness of the shock-absorbing adhesive and high strength of the shock-absorbing structural adhesive.

[0051] Embodiment 1: The shock-absorbing structural adhesive provided by the embodiment of the present invention is composed of the following substances:

[0052] Plasticizer: 187.5g-312.5g;

[0053] PVC paste resin: 135g-225g;

[0054] Nano calcium: 187.5g-312.5g;

[0055] PVC stabilizer: 15g-25g;

[0056] Compound rubber: 67.5g-112.5g

[0057] Epoxy resin: 75g-125g;

[0058] Closed polyamide: 37.5g-62.5g;

[0059] Carbon black: 7.5g-12.5g.

[0060] The shock-absorbing structural adhesive product provided by this embodiment has thixotropy, does not flow at high temperature, and has toughness of the adhesive layer after curing. It is resistant to oil, water, acid and alkali, and heat, has low odor, and has environmental protection performance. Specific shock-absorbing structural adhesive test parameters are shown in Table 1.

[0061] Table 1 Test parameters of the shock-absorbing structural adhesive in the present invention

[0062]

[0063] Embodiment 2: The shock-absorbing structural adhesive provided by the embodiment of the present invention is composed of the following substances:

[0064] Plasticizer: 187.5g;

[0065] PVC paste resin: 135g;

[0066] Nano calcium: 187.5g;

[0067] PVC stabilizer: 15g;

[0068] Compound rubber: 67.5g;

[0069] Epoxy resin: 75g;

[0070] Closed polyamide: 37.5g;

[0071] Carbon black: 7.5g.

[0072] The shock-absorbing structural adhesive product provided in the embodiment of the present invention has the following characteristics, see Table 2.

[0073] Table 2 Product characteristics of shock-absorbing structural adhesive

[0074]

[0075] The test environment is: temperature 23°C / relative humidity 50%.

[0076] Example 3: The shock-absorbing structural adhesive provided by the embodiment of the present invention is composed of the following substances: 312.5 g of plasticizer;

[0077] PVC paste resin: 225g;

[0078] Nano calcium: 312.5g;

[0079] PVC stabilizer: 25g;

[0080] Compound rubber: 112.5g

[0081] Epoxy resin: 125g;

[0082] Closed polyamide: 62.5g;

[0083] Carbon black: 12.5g.

[0084] The shock-absorbing structural adhesive product provided in the embodiment of the present invention has the following characteristics, see Table 3.

[0085] Table 3 Product characteristics of shock-absorbing structural adhesive

[0086]

[0087] The test environment is: temperature 23°C / relative humidity 50%.

[0088] Embodiment 4, as Figure 1 As shown, the method for preparing the shock-absorbing structural adhesive provided by the embodiment of the present invention comprises:

[0089] S1, adding plasticizer, PVC paste resin, nano calcium, mixed rubber and carbon black into a kneader;

[0090] Adjust the speed to 40HZ and knead for 60min;

[0091] S2, discharging and grinding, adjusting the feeding speed of the grinder and the discharging auger speed of the kneader, and putting the mixed materials into the stirring kettle;

[0092] The experimental speed of the grinder is 25-30HZ, which makes the fit smooth;

[0093] S3, adding PVC stabilizer into the stirring kettle and starting the reactor;

[0094] Open the reactor, lower the temperature inside the reactor to below 40°C, add materials, scrape the wall at 15-20HZ, and stir for 60 minutes;

[0095] S4, weighing epoxy resin and blocked polyamide, adding all materials and stirring;

[0096] Scrape the wall at 15-20 Hz and stir for 30 minutes;

[0097] S5, start stirring and start vacuum;

[0098] Adjust the speed to 10-12HZ and vacuum for 90 minutes;

[0099] S6, stop stirring, lift the reactor, scrape off the stirring teeth, and discharge the material into cans.

[0100] The shock-absorbing structural adhesive prepared by the preparation method of the present invention has an adhesive strength exceeding 1 MPa, and the toughness, elasticity, oil resistance, water resistance, acid and alkali resistance, and heat resistance of the adhesive layer after curing are all well reflected.

[0101] For example,

[0102] Polyamide resin is a polycondensation polymer compound with a -CONH structure in the molecule. It is usually obtained by polycondensation of dibasic acid and diamine. The most prominent advantage of polyamide resin is that the softening point range is particularly narrow. Unlike other thermoplastic resins, there is a gradual solidification or softening process. When the temperature is slightly lower than the melting point, it causes rapid solidification. Polyamide resin has good chemical resistance and can resist acids, alkalis, vegetable oils, mineral oils, etc. Because it has polar groups such as amino, carbonyl, and amide groups in its molecules, it has good bonding properties for wood, pottery, paper, cloth, brass, aluminum, and plastics such as phenolic resin, polyester resin, and polyethylene.

[0103] Closed polyamide can be combined with epoxy to enhance adhesion and can react fully with other materials. Therefore, the use of closed polyamide can avoid direct reaction with epoxy at room temperature and unstable properties.

[0104] If epoxy resin is added, the fluidity will be reduced through the reaction of conventional polyamide and epoxy resin, thus causing some problems during processing.

[0105] To this end, the present invention provides a method for preparing a blocked polyamide, comprising:

[0106] Ultrasonic dispersion; stirring dispersion; water bath coating; reflux drying.

[0107] The ultrasonic dispersion comprises: adding the polyamide into a beaker filled with anhydrous ethanol, and then ultrasonicating the polyamide at a power of 1000W for 1h-3h using an ultrasonic instrument.

[0108] The stirring and dispersing comprises: stirring and dispersing the mixed solution with an appropriate amount of organic solvent, the speed of the stirrer is 500r-800r / min, the time is 10-15min, and the organic solvent is one of n-hexane, cyclohexane, benzene, toluene, xylene, petroleum ether, and solvent gasoline.

[0109] The water bath coating comprises: adding the solution after stirring and dispersing into a three-necked flask, stirring and heating in a water bath at 55-85° C. at 300-500 r / min for 2-4 hours to complete the sealing process.

[0110] The reflux drying includes: pouring out the solution after water bath sealing, obtaining the precipitated material by centrifuge, and then drying it in a drying oven at a temperature of 60-85° C. for 6-10 hours. Ethanol and organic solvents are refluxed and recovered according to different boiling points, and the sample is stored at room temperature after drying to obtain a closed polyamide.

[0111] Another example,

[0112] The combination of the PVC paste resin, the PVC stabilizer and the rubber of the present invention provides toughness and elasticity, wherein the introduction of the PVC stabilizer is critical, since PVC is easily thermally degraded at high temperatures, the stabilizer can absorb and neutralize the free radicals generated by thermal decomposition to prevent further breakage of the molecular chain. The antioxidant in the stabilizer can capture the free radicals, and the metal salts in the stabilizer can neutralize the generated acid to avoid further reaction.

[0113] At the same time, PVC stabilizers replace active and unstable substituents; absorb and neutralize HCL released during PVC processing, eliminating the autocatalytic degradation of HCL; neutralize or passivate metal ions and other harmful impurities that catalyze degradation; through various forms of chemical reactions, they can block the continued growth of unsaturated bonds and inhibit degradation and coloring. PVC stabilizer is one of the main auxiliary agents that are indispensable for PVC processing. The amount of PVC stabilizer used is not much, but its role is huge. In PVC processing, the use of PVC composite stabilizers can ensure that PVC is not easy to degrade and is relatively stable. Usually there are:

[0114] 1. Liquid barium zinc composite stabilizer, generally light yellow to yellow-brown oily liquid, specific gravity 1.0-1.1 at room temperature, good heat resistance, not polluted by sulfides, and can be used with epoxy plasticizer to improve the stabilization effect, it has an activation effect on the foaming agent. 2. Liquid calcium zinc composite stabilizer, non-toxic liquid calcium zinc stabilizer's main components are calcium stearate, calcium ricinoleate, zinc stearate, zinc ricinoleate, as well as epoxy soybean oil, ultraviolet absorber, etc. Liquid calcium zinc stabilizer generally uses fatty acid calcium salts and zinc salts with a smaller carbon number that are more soluble in organic solvents. Due to different components and different properties, it is generally a light yellow to yellow clear oily liquid with a specific gravity of 1.0-1.05 at room temperature. It is a non-toxic stabilizer for PVC, mainly used as a stabilizer for food packaging film and utensil foam leather. 3. Liquid barium cadmium and liquid barium cadmium zinc composite stabilizers. This type of composite stabilizer is mainly used in the processing of soft PVC products. The basic components include: (1) Barium salts - can be alkylphenol barium, 2-ethylhexanoic acid barium, lauric acid barium (for powder composite), benzoic acid and substituted benzoic acid barium, neodecanoic acid barium, etc. The barium salt accounts for 6-7% of the composite, that is, the ratio with cadmium salt is about 2:1-32 (in terms of metal, weight percentage, the same below). (2) Cadmium salts - can be 2-ethylhexanoic acid cadmium, lauric acid cadmium, oleic acid cadmium, phenyl acid and substituted benzoic acid cadmium, cyclohexane acid cadmium, neodecanoic acid cadmium, etc. Cadmium salts account for about 3-4% of the composite. (3) Zinc salts - can be 2-ethylhexanoic acid zinc, lauric acid zinc (for powder composite), cyclohexane acid zinc, neodecanoic acid zinc, benzoic acid and substituted benzoic acid zinc, etc. Zinc salts account for 0.5-1% of the composite. (4) Phosphites - can be triphenyl phosphite, diphenyl monooctyl phosphite, diphenyl monodecyl phosphite, tri(nonylphenyl) phosphite, etc. Phosphites account for about 15-20% (by weight) in the complex and are used as chelating agents. (5) Others - including a small amount of phenolic antioxidants and ultraviolet absorbers such as 2,6-di-tert-butyl-p-cresol, bisphenol A, nonylphenol, and liquid paraffin, white oil, diesel, spindle oil and other mineral oils as solvents, and a small amount of defoaming agents such as higher alcohols. Liquid barium cadmium zinc composite stabilizers have different properties due to different compositions. But generally, they are light yellow to yellow clear liquids with a specific gravity of 0.95-1.02 at room temperature, a viscosity of less than 100 centipoise, and a freezing point of about -15°C. Liquid barium cadmium and liquid barium cadmium zinc are similar, both have excellent thermal and light stability, low initial coloring, good transparency and color stability. Their stabilizing effect is stronger than that of solid complex soaps, so the dosage can be reduced, generally 2-3 parts, and dust poisoning will not occur. They are completely dissolved in general plasticizers, have good dispersibility, and have little tendency to precipitate. Among them, the initial coloring of liquid barium cadmium zinc is smaller than that of liquid barium cadmium. 4. Lead salt composite stabilizer has good thermal stability and has been widely used, but the powder of lead salt is fine. During the batching and mixing, its dust can be inhaled by people and cause lead poisoning.

[0115] The embodiment of the present invention provides a method for preparing a PVC stabilizer, comprising: using a symbiotic reaction technology to mix a trisalt, a disalt and a metal soap in a PVC paste resin reaction system with an initial crystal size and various lubricants to ensure that the heat stabilizer is fully dispersed in the PVC paste resin system, thereby preparing a composite lead salt heat stabilizer.

[0116] At the same time, since it is co-melted with the lubricant to form particles, poisoning caused by lead dust is also avoided.

[0117] Trisalt is a chemical substance with the molecular formula 3PbO·PbSO4·H2O. Trisalt products mainly refer to tribasic lead sulfate; its characteristics are white powder, melting point 820℃. It is insoluble in ethanol, soluble in acid and hot ammonium acetate. It is easy to change color and decompose by itself when exposed to light when it is wet. It is used as a stabilizer and colorant for polyvinyl chloride plastic products.

[0118] Lead phosphite, also known as dibasic lead phosphite; disalt, is an inorganic raw material with a molecular formula of HO5PPb3 and a molecular weight of 733.5787. Basic information of molecular structure Chinese name: dibasic lead phosphite English name: Leadphosphite, dibasic Chinese alias: dibasic lead phosphite; the usual preparation includes:

[0119] In the lead oxide method, the metallic lead is first heated and melted in a lead melting furnace, and then sent to a yellow lead furnace for oxidation into lead monoxide. Phosphorus trichloride is added to the reactor and hydrolyzed at 50°C. The temperature is slowly raised and concentrated at 146-148°C. Activated carbon is added for decolorization and filtered to obtain phosphorous acid. The measured lead oxide is first mixed with water to form a slurry and added to the synthesis kettle. It is heated to about 70°C. With acetic acid as a catalyst, a certain amount of phosphorous acid is added under constant stirring. When the pH value reaches 6.9, a white dibasic lead phosphite suspension is generated. A dehydrating agent is added for dehydration. After filtration and drying, the dibasic lead phosphite product is obtained.

[0120] 2Pb+O2→2PbOPCI3+3H2O→H3PO3+3HCI3PbO+H3PO3[Hac]→2PbO+PbHPO3+0.5H2O+0.5H2OLead water method: Add metal lead to the reactor and dissolve it with acetic acid. Slowly add caustic soda solution under stirring to react and generate lead hydroxide. Remove sodium acetate by filtration. Add lead hydroxide to the synthesizer and quantitatively add phosphorous acid under constant stirring to react and generate dibasic lead phosphite. After filtration and drying, the dibasic lead phosphite product is obtained. Its 2Pb(OH)2+H3PO3→this product+2.5H2O.

[0121] Metal soap is a soap made by the reaction of metals other than alkali metals, metal oxides or salts with fatty acids, rosin acid, cyclohexane acid, etc. Metal soap cannot be obtained by direct saponification of oils and fats, but is obtained by double decomposition reaction of fatty acid sodium soap and corresponding metal salt solution, or by melting fatty acids and metal powders.

[0122] The ratio of trisalt, disalt and metal soap can be (1-2):(0.5-2):(1-2).

[0123] The composite lead salt stabilizer contains the heat stabilizer component and lubricant component required for processing, and is called a full-package heat stabilizer. It has the following advantages: (1) The various components of the composite heat stabilizer can be fully mixed during its production process, greatly improving the uniformity of mixing and dispersion with the resin. (2) When the formula is mixed, the number of metering times is simplified, reducing the probability of metering errors and the resulting losses. (3) The supply and storage of auxiliary materials are simplified, which is beneficial to production and quality management. (4) It provides the possibility of dust-free production of products and improves production conditions.

[0124] Application Example 1:

[0125] The present invention provides an application of a shock-absorbing structural adhesive in the bonding of the shock-isolating part of a vehicle body, and the shock-absorbing structural adhesive adopts the shock-absorbing structural adhesive. Its components are as in Examples 1-3;

[0126] Comparative Example:

[0127] A hot melt adhesive for PVC / metal bonding and a preparation method thereof, the hot melt adhesive is prepared from the following raw materials in percentage by weight: polymethyl methacrylate-polybutyl methacrylate-polymethyl methacrylate triblock polymer: 55-75%; amorphous α-olefin copolymer: 10-20%; plasticizer: 3-8%; tackifier: 10-15%; stabilizer: 0.5-2%. The preparation method comprises the following steps: adding polymethyl methacrylate-polybutyl methacrylate-polymethyl methacrylate ternary block copolymer, amorphous α-olefin copolymer, plasticizer, tackifier and stabilizer into an extruder, blending and extruding to obtain the hot melt adhesive for PVC / metal bonding.

[0128] Its bonding performance does not fall off at 80°C for 72 hours, but it does not have the shear strength of 1.5 MPa of the present invention.

[0129] Application Example 2:

[0130] Another object of the present invention is to provide an application of a shock-absorbing structural adhesive in the structural bonding of the seismic isolation part of a workshop component, wherein the shock-absorbing structural adhesive adopts the shock-absorbing structural adhesive, and its components are as in Examples 1-3;

[0131] Comparative Example:

[0132] An expansion seismic isolation adhesive for a body in white comprises the following components by weight percentage: 10-12% of synthetic rubber; 3-5% of butadiene rubber; 3-5% of epoxy resin; 0.2-0.4% of pigment; 37-41% of filler; 2-4% of hygroscopic agent; 1.3-2.5% of curing agent; 0.4-0.6% of foaming agent; 8-12% of additive; 22-27% of plasticizer, wherein the pigment is carbon black. The present invention also provides a preparation method of an expansion seismic isolation adhesive for a body in white, comprising the following steps: Step 1: weighing and batching, weighing each component raw material according to the prescribed measurement, and sequentially putting the weighed raw materials into a 1-ton mixer for batching twice; Step 2: vacuum stirring, vacuum stirring the prepared raw materials; Step 3: viscosity inspection and adjustment, checking the viscosity of the product after the first vacuum stirring, and performing a second vacuum stirring after the inspection to adjust the viscosity, and during the second vacuum stirring, until the product reaches the prescribed performance index and the expansion seismic isolation adhesive finished product is obtained. It has the effect of anti-shearing and shock absorption, but does not have the bonding strength performance of the present invention.

[0133] To further illustrate the effects of the embodiments of the present invention, the following experiment was conducted. The strength of the shock-absorbing structural adhesive provided by the embodiments of the present invention exceeds 1 MPa and is very experiential;

[0134] Follow these steps when using:

[0135] Surface cleaning: Clean the glue application surface to ensure that the surface is clean, free of rust, water, etc.

[0136] Gluing: Use a glue injection gun to apply the product in dots or strips on ribs, body frames and other parts. The diameter of the glue strip should be larger than the sealing gap.

[0137] Curing: Curing at 180℃ for 30min.

[0138] Storage.

[0139] The shock-absorbing structural adhesive product provided in the embodiment of the present invention has the following characteristics, see Table 4.

[0140] Table 4 Product characteristics of shock-absorbing structural adhesive

[0141]

[0142] The test environment is: temperature 23°C / relative humidity 50%.

[0143] The structural shock-absorbing adhesive of the present invention is mainly used for shock-isolating parts of vehicle bodies and workshop parts, such as the bonding and sealing between the outer panels of passenger car doors, engine hoods, and trunk lids and reinforcing plates. It has partial structural bonding effects, shock absorption and sound insulation, and prevents sheet metal warping. The use parts can reduce welding points.

[0144] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principles of the present invention should be covered within the protection scope of the present invention.

Claims

1. A shock-absorbing structural adhesive, characterized in that: The shock-absorbing structural adhesive is composed of the following substances: Plasticizer: 187.5g-312.5g; PVC paste resin: 135g-225g; Nano calcium: 187.5g-312.5g; PVC stabilizer: 15g-25g; Compound rubber: 67.5g-112.5g; Epoxy resin: 75g-125g; Closed polyamide: 37.5g-62.5g; Carbon black: 7.5g-12.5g.

2. The shock-absorbing structural adhesive according to claim 1, characterized in that: The mixed rubber is nitrile.

3. A preparation method, characterized in that: The preparation method is used to prepare the shock-absorbing structural adhesive according to any one of claims 1 to 2, and the method comprises: S1, adding plasticizer, PVC paste resin, nano calcium, mixed rubber and carbon black into a kneader; S2, discharging and grinding, adjusting the feeding speed of the grinder and the discharging auger speed of the kneader, and putting the mixed materials into the stirring kettle; S3, adding PVC stabilizer into the stirring kettle and starting the reactor; S4, weighing epoxy resin and blocked polyamide, adding all materials and stirring; S5, start stirring and start vacuum; S6, stop stirring, lift the reactor, scrape off the stirring teeth, and discharge the material into cans.

4. The preparation method according to claim 3, characterized in that: In step S1, the kneading machine is adjusted to 35-45 Hz for kneading for 60 minutes; in step S2, the grinding machine feed speed is 25-30 Hz.

5. The preparation method according to claim 3, characterized in that: In step S3, the temperature in the reactor is lowered to below 40°C, materials are added, the wall is scraped at 15-20Hz, and stirring is carried out for 60min; in step S4, the scraping speed of stirring is turned on at 15-20Hz, and the stirring time is 30min; in step S5, when stirring is turned on, the rotation speed is adjusted to 10-12Hz; vacuum is turned on for 90min.

6. The preparation method according to claim 3, characterized in that: In step S3, the preparation method of the PVC stabilizer includes: using the symbiotic reaction technology to mix the trisalt, the disalt and the metal soap in the PVC paste resin reaction system with the initial crystal size and various lubricants to ensure that the PVC stabilizer is fully dispersed in the PVC paste resin system to obtain a composite lead salt heat stabilizer, that is, a PVC stabilizer.

7. The preparation method according to claim 3, characterized in that: In step S4, the preparation method of the blocked polyamide includes: ultrasonic dispersion, stirring dispersion, water bath coating, and reflux drying; The ultrasonic dispersion comprises: adding the polyamide into a beaker containing anhydrous ethanol, and then ultrasonicating the polyamide for 1 h to 3 h at a power of 1000 W using an ultrasonic instrument; The stirring and dispersing comprises: stirring and dispersing the mixed solution with an appropriate amount of organic solvent, the speed of the stirrer is 500r / min-800r / min, the time is 10-15min, and the organic solvent is one of n-hexane, cyclohexane, benzene, toluene, xylene, petroleum ether, and solvent gasoline; The water bath coating comprises: adding the solution after stirring and dispersing into a three-necked flask, stirring and heating in a water bath at 55-85° C. at 300-500 r / min for 2-4 hours to complete the sealing process; The reflux drying comprises: pouring out the solution after water bath sealing, obtaining the precipitated material by centrifuge, and then drying it in a drying oven at 60-85° C. for 6-10 hours; and refluxing and recovering ethanol and organic solvent according to different boiling points, and storing the sample at room temperature after drying to obtain a closed polyamide.

8. Application of a shock-absorbing structural adhesive in the bonding of the shock-isolating part of a vehicle body, characterized in that: The shock-absorbing structural adhesive adopts the shock-absorbing structural adhesive described in any one of claims 1-2.

9. Application of a shock-absorbing structural adhesive in the structural bonding of seismic isolation parts of workshop components, characterized in that: The shock-absorbing structural adhesive adopts the shock-absorbing structural adhesive described in any one of claims 1-2.

Citation Information

Patent Citations

  • Composite modified epoxy resin structural adhesive and preparation methods of composite modifier and structural adhesive

    CN108048007A